Pineapple Waste Processing Design as Functional Food to Support Agrotourism in East Lombok, Indonesia: Desain Pengolahan Limbah Nanas sebagai Makanan Fungsional untuk Mendukung Agrowisata di Lombok Timur, Indonesia - Ayu, Hanifah; Wardatullatifah S, Ince Siti; Hidayat, Syahroni; Jannah, Mirriyadhil (Indonesian Journal of Tropical Biology, 2025)
The abundant pineapple waste in East Lombok remains underutilized as a functional food resource and has not been integrated into sustainable agrotourism development, leading to environmental challenges and missed economic opportunities for local communities. This study aims to design a model for converting pineapple waste into functional food products within a zero-waste agrotourism and circular economy framework that supports community-based development. A descriptive qualitative literature review was conducted using reputable journals, BPS statistics, data from agricultural and tourism agencies, and regional planning documents. Thematic analysis identified the bioactive potential of pineapple waste, explored functional product innovations, and formulated integration schemes for agrotourism activities. The results show that pineapple peel, core, and crown contain bromelain, phenolic compounds, and dietary fiber that can be processed into fermented beverages, functional vinegar, peel tea, fiber flour, and high-fiber snacks suitable as agrotourism products. Integrating these products through workshops, demonstrations, tasting sessions, educational tours, and souvenir sales can enhance commodity value, strengthen green destination branding, and support the SDGs. Overall, the utilization of pineapple waste offers a synergistic strategy that links agriculture, food innovation, sustainability, and tourism. The study highlights the need to establish a circular economy–based pineapple agrotourism pilot model supported by product guidelines, food safety standards, innovation facilities, and collaboration among farmers, MSMEs, researchers, and local government.